Autonomy Promotion in a Multiethnic Context: Reflections on some normative issues - Désy, Michel (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2010)
The concept of health promotion enshrined in the Ottawa Charter grants an important place to autonomy. However, it is not clear that health broadly defined and autonomy are related in the sense intended by the authors of the Charter. Moreover, promotion of autonomy towards groups who do not consider it as a core value remains a problem. This paper presents a concept of autonomy and promotion that provide a partial answer to this problem. Examples of public policy in a multiethnic context are given to illustrate how the proposed conception of autonomy promotion differs from more coercive policies.